Very late-onset neuromyelitis optica spectrum disorder presenting with falls and monoparesis: A case report - Pannathat Soontrapa (2019)
© 2018, Medical Association of Thailand. All rights reserved. Here, we report a case of very late-onset neuromyelitis optica spectrum disorder [NMOSD] in an 83-year-old female who presented with monoparesis at right leg and subsequent falling that resulted in right femoral neck fracture. The patient was initially diagnosed as having lumbar spondylosis with radiculomyelopathy. As the disease progressed, she developed quadriparesis that resulted from extensive transverse cervical myelitis with positive anti-aquaporin-4 antibody. This finding helped to guide us to a diagnosis of NMOSD. Accordingly, any patient, regardless of age, that presents with extensive transverse myelitis should be considered as NMOSD.